SAT-490 A Case of Unilateral Exophthalmos Due to Thyroid Orbitopathy and Its Association with Chronic Kidney Disease - Muammar, Ahmad R (J Endocr Soc, 2020)
Graves ophthalmopathy(GO)is the most common extra-thyroidal manifestation of Graves’ disease (GD). Most cases of GO are bilateral which may be asymmetric, whereas unilateral ophthalmopathy is less common and has been observed in 9-15% cases. Association between chronic kidney disease and unilateral Grave’s ophthalmopathy in a clinically euthyroid patient is rare. We report a case of a 24-year-old male with no previous history of any chronic medical illnesses who presented with protruded right eye for the past 6 months. He did not have any other visual symptoms or symptoms related to thyroid disease. Laboratory results revealed low TSH, normal free T3 and free T4. TSH receptor antibodies were positive. He also had elevated serum creatinine at 418 umol/L (normal levels 64 - 110 umol/L). US KUB showed bilateral small sized kidneys and increased parenchymal echogenicity suggestive of chronic kidney disease. MRI Head showed features suggestive of unilateral thyroid associated orbitopathy. Patient received 1-week course of oral prednisolone 10 mg per day after which his exophthalmos improved.Case report: A 24 year old male with no previous history of any chronic medical illnesses, presented to the clinic with protruded right eye for the past 6 months that was progressively getting worse. There was no eye pain, visual changes, ophthalmoplegia, dryness or discharge from eye. Patient did not report any other symptoms, Physical examination revealed a comfortable man with protruded right eye, lid retraction, normal eye movements and no signs of orbital cellulitis. Neck examination was significant for a mild diffuse goitre. Laboratory studies were significant for haemoglobin of 12.1 g/dl (normal 13-17 g/dl). He also had elevated serum creatinine at 418 umol/L (normal 64 - 110 umol/L). Serum electrolytes, liver function tests and lipid profile were within normal range. 24 hr urine collection showed 3.08 gm/24 hr proteinuria. Serum TSH was 0.04 mIU/L (normal 0.45 - 4.5 mIU/L), free T4 was 13.8 pmol/L (normal 9 - 20 pmol/L) and free T3 was 4.56 pmol/L (normal 2.89 - 4.88 pmol/L). Thyrotropin Receptor Ab titre was 4.69 IU/L (normal 0.00 - 1.75 IU/L). ANA, ANCA, C3, C4, Anti thyroid peroxidase and Anti GBM antibodies were negative. Screening for hepatitis B, C and HIV was negative US KUB showed bilateral small sized kidneys and increased parenchymal echogenicity suggestive of CKD. MRI Head was remarkable for proptosis of the right eye with increased retro-orbital fat, thickening and T2 hyper-intensity with sparing of the tendinous insertion involving the right inferior, medial, superior and lateral rectus muscles with crowding at the orbital apex. Features were suggestive of unilateral thyroid associated orbitopathy. Patient received 1-week course of oral prednisolone 10 mg per day after which his exophthalmos improved. An association between CKD and GO in a clinically euthyroid patient is rare.